(untitled) (Journal of Forestry, 2024)
The objective of this study was to determine the antioxidant activity and total phenolic content of fresh and dried rosemary leaves from urban and rural areas and to compare the results with those of a commercial sample. Rosemary plant material (R. officinalis) was collected during May and June 2024 in the summer/sunny period. The homogenized samples were macerated at room temperature using distilled water and a 70% ethanol solution. The total phenolic content was determined using the Folin-Ciocalteu method, while antioxidant activity was assessed using the DPPH scavenging method and expressed as Trolox equivalents (µmol TE/g). The total phenolic content ranged from 36.11 ± 0.96 to 233.07 ± 1.66 mg GAE/g, depending on the type of solvent used and the state of the plant material. Based on the collected data, it can be concluded that using 70% ethanol significantly increases the efficiency of total phenolic extraction from rosemary. The highest antioxidant activity values were found in ethanol extracts (712.70 ± 1.90 – 934.06 ± 0.77 µmol TE/g), regardless of the provenance of plant material (urban/rural) or sample state (dry/fresh). Water extracts showed lower antioxidant activity values, regardless of the provenance and sample state (164.13 ± 4.04 to 247.30 ± 3.56 µmol TE/g), with the commercial sample water extract standing out (867.70 ± 1.98 µmol TE/g). One-way ANOVA testing revealed no difference in antioxidant activity between samples from urban and rural areas (0.317 > 0.05), but there was a difference in the total phenolic content of the analyzed samples (0.015 < 0.05). T-test results indicated a difference in antioxidant activity based on the use of different solvents in the extraction process (0.013 < 0.05), but not in the total phenolic content (0.137 > 0.05).